INTELLIGENT STRUCTURING OF RUSSIAN TEACHING TEXTS IN A DIGITAL EDUCATIONAL ENVIRONMENT FOR A TURKIC-SPEAKING AUDIENCE (Uzbekistan Open Conference, 2026)
The theses address the problem of how students in a Turkic-speaking audience understand Russian teaching texts. The paper emphasizes that comprehension difficulties are related not only to vocabulary and grammar but also to the way ideas are developed, the discourse-syntactic organisation of the text, the linear-thematic organisation of the paragraph, and the distribution of core and explanatory information. It is argued that digital and intelligent structuring of teaching texts can become an effective tool for pedagogical adaptation in a multilingual educational environment only if the restructuring is carried out with due regard for the discourse-syntactic norms of Turkic languages and their typical patterns of paragraph development.